INTERPRETASI TUJUH HARI SIDANG PRAPERADILAN ANTARA HARI KERJA DAN HARI KALENDER DALAM BEBERAPA KASUS PRAPERADILAN DI PENGADILAN NEGERI PEKANBARU - Orde Prianata; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The pretrial hearing is conducted quickly and the minutes and pretrial decisionsare made like a brief examination and are chaired by a single judge. Seven days is aprovision mandated by the Criminal Procedure Code for the implementation of a quickand simple pre-trial series, starting from the commencement of the examination. TheConstitutional Court through decision number 78 / PUU-XI / 2013 asserted that at thelatest seven days the pretrial process is to provide legal certainty, especially forapplicants who feel their rights are harmed.This type of research is empirical juridical research that is as an effort toapproach the problem under study with the nature of law that is real or in accordancewith the reality in the field, because in this study, researchers immediately conductresearch on the location or place under study to provide a complete and clear pictureabout the problem under study. The nature of this research is descriptive. This studyuses secondary data, namely data that has been prepared.The results of this study are the interpretation of judges related to the seven-daypretrial hearing between workdays and calendar days in some cases and theirrelevance to the judge's code of ethics in the Pekanbaru District Court varies. There arestill interpretations of judges who are not in accordance with the provisions of theKUHAP so that there are still judges who decide that pretrial cases exceed 7 workingdays. Fulfillment of the right of the applicant with a related interpretation of the sevendaypretrial hearing between the working day and calendar day in the PekanbaruDistrict Court still contains several cases that indicate the fulfillment of the right of theapplicant in accordance with the provisions in the Criminal Procedure Code. In Article82 paragraph (1) letter c KUHAP no later than seven days the judge must have made adecision, while there are still a number of cases where the judge's decision is imposedmore than 7 days.Keywords: interpretation, seven days trial, pretrial.